Peran Marhabanan Terhadap Solidaritas Ekonomi Masyarakat Perum Taman Pelangi Kab. Cirebon: Peran Marhabanan Terhadap Solidaritas Ekonomi Masyarakat Perum Taman Pelangi Kab. Cirebon - Kurniawan, Heru; Pranitamotik, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The characteristics of residents in housing tend to be individualism where they view all activities as being carried out by their own abilities without seeing social social as part of life. The purpose of this service is to apply marhabanan activities in fostering the solidarity attitude of the housing community, which is generally individualistic. which is generally Individualism, this service was carried out at Perum Pelangi, Cirebon Regency for 1 month and 12 days. The results of this service-based research show that individualism can be minimised through marhabanan activities by cooperating with each resident continuously. marhabanan activities that have been running lead to good social solidarity, this can be seen from the mutual activity. social solidarity, this can be seen from mutual cooperation in various programmes related to religion and the environment. programmes related to religion and the neighbourhood, and economic solidarity can be seen from the increasing number of users of services and products. economic solidarity can be seen from the increasing number of users of the services and products of the surrounding community housing